Belly Dancer’s Dyskinesia: A Rare Phenomenon (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2024)
Belly dancer’s dyskinesia (BDD), also known as diaphragmatic flutter or diaphragmatic myoclonus is a distinctive and rare movement disorder characterized by involuntary and rhythmic movements of the abdominal muscles resembling belly dance. This phenomenon has a variable clinical presentationthereby making it difficult to diagnose. It is observed in various clinical scenarios, including post-stroke, psychiatric, and chronic neurological disorders, and as adverse effect of certain medications.A high index of suspicion is required in a patient with symptoms including abnormal abdominal wall movements, dyspnoea and respiratory distressfor an early diagnosis of this entity. We report an unusual case of BDD secondary to 5HT3-antagonist use in a patient with multidrug resistant tuberculosis (MDR TB).